Vaping, SARS-CoV-2, and Multisystem Inflammatory Syndrome: A Perfect Storm - Brar, Esha; Saxena, Anish; Dukler, Claudia; Xu, Fangxi; Saxena, Deepak; Cheema Brar, Preneet; Guo, Yuqi; Li, Xin (Frontiers in Pediatrics, 2021)
The use of electronic cigarettes (e-cigarettes) and vaping among adolescents has risen exponentially in the last decade. E-cigarette flavors has driven adolescents to use these convenient, USB-like devices, designed to create a desired social image, while being seemingly unaware of the serious health consequences of their behavior. Vaping impacts protective pulmonary barriers by attenuating the mucociliary clearance and by increasing peribronchial inflammation and fibrosis. The recent SARS-CoV-2 (COVID-19) pandemic has been characterized by a plethora of unusual disease presentations. Among them, a unique presentation seen exclusively in children and adolescents was multisystem inflammatory syndrome (MIS-C). Seventy percent of adolescents who had MIS-C also had acute respiratory distress syndrome (ARDS), and we speculate that there may exist common denominator that links MIS-C and adolescents: the use of e-cigarettes. The virus targets the angiotensin converting receptor (ACE receptor), and studies have shown nicotine-based e-cigarettes or vaping cause oxidative stress and resulting in the upregulation of ACE2, which might worsen ARDS in MIS-C. Our mini-review highlights that adolescents using e-cigarette have alterations in their pulmonary defenses against SARS-CoV-2: an upregulation of the ACE2 receptors, the primary target of SARS-CoV-2. Their compromised immune system makes them more uniquely vulnerable to Covid-19 related MIS-C, increasing their risk for ARDS and related morbidities. Currently, studies have shown an association between MIS-C and vaping, we speculate that adolescents who vape/smoke might be especially vulnerable to serious respiratory symptoms if they develop a hyper-inflammatory state MIS-C.